ANALISIS HUBUNGAN ANTARA BERBAGAI DIMENSI SIKAP INDIVIDUAL DALAM MENGELOLA KELUARGA DAN KARIER - Nuryati Nuryati (KINERJA, 2005)
This research aims to analyze relationship between individual attitude to the managing family and career. This study is based on Sander M. M., Lengnick-Hall, C. A., Lengnick-Hall, M. L., & Steele-Clapp, L. (1998) study. Data for this study were provided by 217 students of the last level of Universities taken from state and private Universities at Yogyakarta. Individual attitude is measured by using CFAM from Sander et al. (1998). Response rate of this study was 95,2%. The data were analized by correlationanalysis. This study found eight important results. First, spousal supports and dominances, is positively corrrelated with other scales. Second, for the males and females, is positively correlated significantly between spousal suppports and balances. Third, for the males, is positively correlated significantly between family focus and career focus, whereas it was not for the females. Fourth, for the males, is positively correlated significantly between career focus and balances, whereas it was not for the females. Fifth, for the males, is positively correlated significantly between independences and family focus, whereas it was not for the females. Sixth, for the males and females, is significantly uncorrelated between independences and career focus. Seventh, for the males and females, is significantly uncorrelated between independences and dominances. Eighth, for the males and females, is significantly uncorrelated between independences and spousal supports.Keywords: individual attitude, CFAM(career-family attitudes measures), correlation analysis.